Influences of leaf cutting on growth and yield of rice - Khatun, M Mahmuda; Ali, M Hazrat; Mateo, Lun G (Journal of Bio-Science, 2012)
No Abstract availabe DOI: http://dx.doi.org/10.3329/jbs.v19i0.13008 J. bio-sci. 19 99-100, 2011